2012
DOI: 10.1128/aac.00431-12
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adhesion Forces with Substratum Surfaces and the Susceptibility of Biofilms to Antibiotics

Abstract: bBiofilms causing biomaterial-associated infection resist antibiotic treatment and usually necessitate the replacement of infected implants. Here we relate bacterial adhesion forces and the antibiotic susceptibility of biofilms on uncoated and polymer brushcoated silicone rubber. Nine strains of Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa adhered more weakly to brush-coated silicone rubber (؊0.05 ؎ 0.03 to ؊0.51 ؎ 0.62 nN) than to uncoated silicone rubber (؊1.05 ؎ 0.46 to ؊5.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…32 Another in vitro study demonstrated that S. aureus, S. epidermidis and P. aeruginosa possess strong forces of adhesion to foreign bodies. 33 In studies of implants from patients having revision for total joint arthroplasty of hip or knee without clinical and routine microbiological evidence of infection, bacterial biofilms including coagulase- negative staphylococci were isolated from the removed implants by using ultrasonication and other sensitive methods, 34,35 indicating a biofilm infection of the implant. Bacteria usually form biofilm on foreign bodies that are placed in patients for medical reasons, such as peripheral and central venous catheters, heart valves, ventricular assisting devices, coronary stents, arthro-prostheses, fracture-fixation devices, breast implants, intraocular lenses, dental implants, etc.…”
Section: Possible Causes Leading To Prosthesis-related Infectionsmentioning
confidence: 99%
“…32 Another in vitro study demonstrated that S. aureus, S. epidermidis and P. aeruginosa possess strong forces of adhesion to foreign bodies. 33 In studies of implants from patients having revision for total joint arthroplasty of hip or knee without clinical and routine microbiological evidence of infection, bacterial biofilms including coagulase- negative staphylococci were isolated from the removed implants by using ultrasonication and other sensitive methods, 34,35 indicating a biofilm infection of the implant. Bacteria usually form biofilm on foreign bodies that are placed in patients for medical reasons, such as peripheral and central venous catheters, heart valves, ventricular assisting devices, coronary stents, arthro-prostheses, fracture-fixation devices, breast implants, intraocular lenses, dental implants, etc.…”
Section: Possible Causes Leading To Prosthesis-related Infectionsmentioning
confidence: 99%
“…Given the similar hydrophilic characters of both alginate lyase and BSA coatings via polydopamine, results suggest that alginate lyase may have another underlying mechanism for preventing bacterial adhesion, beyond preventing nonspecific adhesion. The combination of this preventive approach with therapeutic approaches, namely, antibiotic therapies may hold great potential to fight biomaterial‐associated infections, as it is expected that bacterial cells adhered to these modified surfaces will be more susceptible to antibiotic therapy in a similar way to bacteria that adhered more weakly to brush‐coated silicone rubber, enhancing their susceptibility to gentamicin treatment …”
Section: Resultsmentioning
confidence: 99%
“…The combination of this preventive approach with therapeutic approaches, namely, antibiotic therapies may hold great potential to fi ght biomaterial-associated infections, as it is expected that bacterial cells adhered to these modifi ed surfaces will be more susceptible to antibiotic therapy in a similar way to bacteria that adhered more weakly to brushcoated silicone rubber, enhancing their susceptibility to gentamicin treatment. [ 45 ]…”
Section: Antibacterial Performance Of Surfaces Functionalized With Almentioning
confidence: 99%
“…Yet it is known that also low numbers of bacteria adhering on a polymer brush coating have the ability to grow over prolonged periods of time into weakly adhering microcolonies. The weak adhesion does not stimulate the transition to a biofilm mode of growth, leaving bacteria potentially in a more antibiotic susceptible state . Our modular coating concept allows to kill these bacteria as soon as they approach the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The weak adhesion does not stimulate the transition to a biofilm mode of growth, leaving bacteria potentially in a more antibiotic susceptible state. [22] Our modular coating concept allows to kill these bacteria as soon as they approach the surface. To this end, the VS-module was complemented with the possibility of sustained CHX release.…”
Section: Discussionmentioning
confidence: 99%